HYPERELLIPTIC GRAPHS AND METRIZED COMPLEXES - YOAV LEN (Forum of Mathematics, Sigma, 2017)
We prove a version of Clifford’s theorem for metrized complexes. Namely, a metrized complex that carries a divisor of degree